Teenagers’ perceptions of teacher attitudes and the influence of teacher attitudes on students’ lives in state schools - Yolak, Reneta Sibel. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
The aim of this qualitative study was to investigate the perceptions of teacher attitudes and the influence of teacher attitudes on high school students’ lives in state schools in Turkey. This study was conducted in Beykoz via semi-structured interviews of 36 high school students from five Anatolian schools who had low socioeconomic status. Constant comparative method was used for data analysis. The findings of the study exposed that, the attitudes of the teachers changed the students’ lives in different ways. A positive relationship (compassionate, tolerant, patient and optimistic teacher attitudes) has impact on teenagers’ lives such as increasing their self-efficacy and self-confidence, causing the students to love the lessons in such a way to encourage them to go on with further studies, and increasing their academic success. Receiving a positive attitude from a teacher can also help students to socialize, develop their personalities, recognize and improve their abilities, potentials, and personal qualities. In contrast, students expressed that irresponsible, selfish, loveless, insulting, biased, unjust teacher attitudes led to psychological problems of students, low academic success, low self-efficacy, and low self-confidence. By examining and analyzing student perceptions, judgments, decisions, and recommendations can be made for future improvements on teacher and counselor training.
Keywords: College students -- Attitudes.; Teacher-student relationships.